Rozwiąż równanie
Zad. 4
a) x(x²-4x)=0
b) x(4x²+x)=0
c) (x²-x)(x+2)=0
d) (x²+x)(x-6)=0
e) (2x²-x)(2x+1)=0
f) (4x²-x)(6x-2)=0​


Odpowiedź :

Zad. 4

a)

x(x² - 4x) = 0

x²(x - 4) = 0

x² = 0 lub x - 4 = 0

x = 0 lub x = 4

Odp. x = 0 lub x = 4

b)

x(4x²+ x) = 0

x²(4x + 1) = 0

x² = 0 lub 4x + 1 = 0

x = 0 lub 4x = - 1   |:4

x = 0 lub x = - ¹/₄

Odp. x = - ¹/₄ lub x = 0

c)

(x²- x)(x + 2) = 0

x(x - 1)(x + 2) = 0

x = 0 lub x - 1 = 0 lub x + 2 = 0

x = 0 lub x = 1 lub x = - 2

Odp. x = - 2 lub x = 0 lub x = 1

d)

(x² + x)(x - 6) = 0

x(x + 1)(x - 6) = 0

x = 0 lub x + 1 = 0 lub x - 6 = 0

x = 0 lub x = - 1 lub x = 6

Odp. x = - 1 lub x = 0 lub x = 6

e)

(2x² - x)(2x + 1) = 0

x(2x - 1)(2x + 1) = 0

x = 0 lub 2x - 1 = 0 lub 2x + 1 = 0

x = 0 lub 2x = 1   |:2 lub 2x = - 1   |:2

x = 0 lub x = ¹/₂ lub x = - ¹/₂

Odp. x = - ¹/₂ lub x = 0 lub x = ¹/₂

f)

(4x² - x)(6x - 2) = 0​

2x(4x - 1)(3x - 1) = 0

2x = 0   |:2 lub 4x - 1 = 0 lub 3x - 1 = 0

x = 0 lub 4x = 1   |:4 lub 3x = 1   |:3

x = 0 lub x = ¹/₄ lub x = ¹/₃

Odp. x = 0 lub x = ¹/₄ lub x = ¹/₃